PERSECUȚIE ȘI INTEGRITATE CREȘTINĂ DIN PERSPECTIVA LUI HIPOLIT (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
Hippolytus’ Perspective on Christian Integrity During the PersecutionHippolytus (170-235) was a Church Father who wrote several exegetical works on Holy Scripture. During the persecution of Emperor Septimius Severus, he wrote a treatise on the Antichrist and a Commentary on Daniel. In both works he encouraged the Christians to remain faithful in persecution, even if they would loose their lives. God’s sovereignty was the main reason presented by Hippolytus for which the Christians had to be firm during the persecution. God is sovereign and his plan with all people is being fulfilled. If God allows a Christian to be martyred, it is better for him because he is no longer exposed to temptation and has eternal life guaranteed. If God saves a disciple from death, he does so to demonstrate that He is able to save a believer and for the glory and the proclamation of His Name. Therefore, for Hippolytus, God’s sovereignty is the foundation of Christian integrity when religious freedom is threatened.